Bureaucratic Reform in the Secretariat General of the Indonesian House of Representatives (2020–2024): Case Study of Increasing the Bureaucratic Reform Index Through the Kotter Change Management Approach - Imama, Muhamad Aaqil; Zainal, Veithzal Rivai; Azis Hakim (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study analyzes the implementation of bureaucratic reform in the Secretariat General of the Indonesian House of Representatives in the 2020–2024 period using John P. Kotter's organizational change model. Data were collected from official documents of the DPR RI Secretariat General's performance, the bureaucratic reform pocket book, and the 2020–2024 Renstra strategic document. This study found that the DPR RI Secretariat General succeeded in showing an increase in the Bureaucratic Reform Index (IRB) value from 76.63 (2020) to 84.63 (2024) . This study aims to identify and analyze Human Resource Management (HRM) initiatives that have been implemented and formulate strategic recommendations for improving the IRB in the future . This study highlights the effectiveness of Kotter's eight stages of change in driving bureaucratic improvement through creating urgency, coalition building, developing a vision, communicating change, empowering employees, achieving quick wins, consolidating success, and institutionalizing change. A qualitative approach with a case study method was used, supported by an analysis of official performance report documents and a review of relevant HRM literature. The research findings are expected to provide theoretical and practical contributions to the development of HR in the context of effective change strategies in bureaucratic reform in the public sector.